Sosialisasi Fungsi Tuha Peut dalam Menyusun Rencana Kerja Pembangunan Gampong Ujong Drien - Sopar Sinambela; Arfriani Maifizar (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
Gampong is the lowest government in the government system in Indonesia. In recent years, gampongs or villages have been given great authority in implementing village governance, especially in preparing village / gampong development plans. In implementing the gampong government, the keuchik who leads the gampong government, apart from being assisted by the village secretary and gampong apparatus, is also assisted by a customary institution known as Tuha Peut. One of the functions of tuha peut is given the authority to carry out the joint development planning function with the village keuchik as outlined in the RKPG document. The socialization of tuha peut functions in gampong governance is necessary to provide an in-depth understanding of the duties and functions of tuha peut as partners of the gampong government in implementing the wheels of government and development. The formulation of the problem in this activity is limited to the socialization of tuha peut's function in compiling a work plan for village development (RKPD / G). The method used in this service is a qualitative method through the Focus Group Discussion (FGD). Keywords: Socialization, Tuha Peut Gampong, Village Development Work Plan